Reference Price for the Mexican Crude Oil Mix Export Price: An Alternative Estimation for the Budget and Fiscal Responsibility Law - David, Alberto Gallegos; Valdes, Arturo Lorenzo; Becerril, Barbara Trejo (International Journal of Energy Economics and Policy, 2022)
This paper aims to perform an alternative methodology the Ministry of Finance and Public Credit (SHCP) applies to estimate the annual Mexican Crude Oil Mix Export Price (MXM), a crucial element of the General Economic Policy Criteria in the Economic Package. We first identify the MXM and the West Texas Intermediate (WTI) relation, computing tail conditional dependence between both series. Subsequently, we use a market risk analysis approach that considers some methodologies to estimate the value at risk (), including an ARIMA-TGARCH model for the innovations of the MXM's price to forecast its behavior using data daily data from January 3rd, 1996, to December 30th, 2021. Once we identify the VaR and the ARIMA-TGARCH components, we aim to design an alternative method to estimate the annual average MXM's price.